VERBS AND PHENOMENON VARIATIONS IN MENTAL PROCESS - Rahmasari, Gartika (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2018)
The objectives of this research are to describe what participants used to indicate which verbs included in mental processes, and to list and describe what verbs used and phenomenon variations found in mental processes. The analysis is performed mainly based on theory of functional grammar written by Haliday, Eggins, Gerot, Lock, and Martin. The data are taken from an English novel entitled Eclipse by Stephenie Meyer. Method used in this research is content analysis conducted in three steps: looking for certain symbols, making classification based on certain criteria, and making some prediction using analysis technique, that is functional grammar. The result of this research shows that there are three main classifications that show what phenomenon variants that can be found in mental process, (1) Phenomenon of thing, (2) Phenomenon of fact, and (3) phenomenon of thought. Based on mental process data containing phenomenon of thing, the verbs that can be found include appreciate, decide, suppose, suspect, believe, consider, guess, imagine, know, quail, realize, recognize, remember, remind, think, understand, wonder, occur to, contemplate, and ponder.